Dopants modulate crystal growth in molten salts enabled by surface energy tuning. Issue 35 (16th June 2021) - Li, Xiaoqiao; Zhou, Linming; Wang, Han; Meng, Dechao; Qian, Guannan; Wang, Yong; He, Yushi; Wu, Yongjun; Hong, Zijian; Ma, Zi-Feng; Li, Linsen
Abstract : Dopants traditionally used for modifying crystal lattices can also function as growth mediators in molten salt synthesis and enable a high energy-density, high power LiCoO2 cathode for lithium-ion batteries. Abstract : Crystalline materials are routinely produced via high-temperature synthesis and show size-dependent properties; however, a rational approach to regulating their crystal growth has not been established. Here we show that dopants traditionally used for modifying crystal lattices can also function as growth mediators in molten-salt synthesis by altering the surface energy and thus the nucleation barrier and the critical nuclei size. This was demonstrated by size-tunable synthesis of lithium cobalt oxide (LiCoO2 ) with a trace amount of titanium oxide or tungsten oxide as the dopant. The understanding of the dopant-mediated growth mechanism allows the rational design and control of the particle size and the doping for LiCoO2, enabling a high energy-density battery cathode with exceptional rate capability and cycle stability at high voltages intolerable for conventional LiCoO2 .